4. Os resultados de (2 + 4), (2 – 4), (-2 + 4) e (-2 – 4) são, respectivamente:
a) 6, -2, 2, -6
b) 6, -2, -2, -6
c) 6, 2, 2, 6
d) 6, 2, -2, 6
Soluções para a tarefa
Respondido por
16
Resposta:
a)
Explicação passo-a-passo:
( 2 + 4 ) = 6
( 2 - 4 ) = - 2
( -2 + 4 ) = 2
( -2 - 4 ) = - 6
Respondido por
9
Resposta:
a)
Passo-a-passo:
( 2 + 4 ) = 6
( 2 - 4 ) = - 2
( -2 + 4 ) = 2
( -2 - 4 ) = - 6
BONS ESTUDOS !
Perguntas interessantes
História,
10 meses atrás
Matemática,
10 meses atrás
Inglês,
1 ano atrás
História,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás